Influence of the Covid-19 pandemic on cerebrovascular diseases in the Sao Paulo region of Brazil - Raiene Telassin Abbas-Kayano; Yara Hahr Marques Hökerberg; Raquel de Vasconcellos Carvalhaes de Oliveira (Communications Medicine, 2025)
Abstract Background The rapid spread of covid-19 overwhelmed healthcare systems. This study aimed to investigate the impact of the covid-19 pandemic on hospitalizations and hospital deaths due to cerebrovascular diseases (CVD) in São Paulo state, Brazil. Methods This ecologic study evaluated the CVD hospitalizations and hospital deaths (2017–2021) by demographic features and CVD type. During the pandemic (2020–2021), segmented regression models were used to detect changes in CVD trends. We also evaluated the detrended cross-correlation between CVD deaths and hospitalization with the SARS-Cov-2 infection series. Results During the pandemic, there is a 35% reduction in CVD hospitalizations, mainly in elective admissions and ischemic stroke, but a 6.5% increase in deaths, especially in Black and Brown individuals, and those aged 20–29 years. From 2020 to 2021, Black and Brown individuals experience an earlier and more prolonged increase in hospital deaths. Ischemic CVD hospitalizations decrease in the first quarter of 2020. Older people exhibit a monthly increase of 2.9% in hospitalizations and 5.3% in deaths in the 2nd and 3rd quarters of 2021. SARS-Cov-2 infections are inversely correlated to CVD hospitalizations and directly correlated to CVD hospital deaths. Conclusions Covid-19 pandemic negatively affects CVD hospitalizations and deaths, particularly in Black and Brown individuals. The decrease in hospitalizations and increase in hospital deaths of ischemic CVD highlights vulnerability in accessing healthcare resources during the pandemic.